Beyond physical entrainment: competitive and cooperative mental stances during identical joint-action tasks differently affect inter-subjective neural synchrony and judgments of agency. (3rd May 2020) - Cho, Philip S.; Escoffier, Nicolas; Mao, Yinan; Green, Christopher; Davis, Richard C.
ABSTRACT: Little work has examined how mental stance alone, apart from physical entrainment, affects between-participant neural synchrony during joint social interaction. We report the first findings on how cooperative and competitive mental stances, even during identical visuomotor joint-action tasks, result in distinct neural oscillatory signatures in low beta and theta band between-participant phase synchrony. Two participants jointly controlled a cursor and were instructed to either compete or cooperate to move it to one of three targets. The visuomotor output was identical for both the compete and cooperate conditions because participants were privately given the same target for experimental trials. Cooperation enhanced theta band between-participant phase-locking value (PLV) midtrial at 1-2 seconds, reflecting activation of systems for social coordination to move the cursor in a shared direction. Competition enhanced low beta between-participant PLV, shifting from temporal to frontal regions, indicating that participants focused only on their target and later evaluated self-agency as winner or loser. This interpretation of the neural signature was corroborated by participants' greater post-trial ratings of the degree of control over the cursor during competition. Top-down cooperative and competitive mental stances shape perceptions of social context and affect interpersonal neural synchrony important for representation of self and others' actions.